Oxygen Reduction Activity on Perovskite Oxide Surfaces: A Comparative First-Principles Study of LaMnO3, LaFeO3, and LaCrO3 - Wang, Yan; Cheng, Hai-Ping (Journal of physical chemistry. C, 2013)
The understanding of oxygen reduction reaction (ORR) activity on perovskite oxide surfaces is essential for promising future fuel cell applications. We report a comparative study of the ORR mechanisms on LaBO3 (B = Mn, Fe, Cr) surfaces by first-principles calculations based on density functional theory (DFT). Results obtained from varied DFT methods such as generalized gradient approximation (GGA), GGA+U and the hybrid Hartree–Fock density functional method are reported for comparative purposes. We find that the results calculated from hybrid-functional method suggest that the order of ORR activity is LaMnO3 > LaCrO3 > LaFeO3, which is in better agreement with recent experimental results (Suntivich et al., Nature Chemistry 2011, 3, 546) than those using the GGA or GGA+U method.